Spatial analysis of ecological risk in a coastal dune landscape using high resolution aerial photography - ListyaNiNgrum, Noviyanti; Mardiatno, Djati; Pangaribowo, Evita Hanie; Setiawan, Muhammad Anggri; Sartohadi, Junun; Sulistyo, Bambang (Quaestiones Geographicae, 2024)
This study aims to investigate the dynamic pattern of landscape ecological units (LEUs) and analyse spatial variations of the ecological risk in Parangtritis coastal dune, Yogyakarta, Indonesia. A quantitative method was used in this research as part of landscape ecological analysis using a geographic information system. LEUs were interpreted by small format aerial photographs (SFAPs) and verified through field survey, then were calculated using the formula within grids to produce the ecological risk index (ERI) in the total area. According to the sub-class and class scenario, many LEUs showed changes in their landscape pattern. The ERI in the study area consisted of five levels (very low to very high), each of which was spatially varied. The ecological risk formed clusters coinciding with certain LEUs where fragility chiefly contributed to the sub-class scenario, while disturbance contributed to the class scenario.